2020
DOI: 10.3390/ijms21218196
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Single Nucleotide Polymorphisms on Autophagy-Related Genes

Abstract: In recent years, the study of single nucleotide polymorphisms (SNPs) has gained increasing importance in biomedical research, as they can either be at the molecular origin of a determined disorder or directly affect the efficiency of a given treatment. In this regard, sequence variations in genes involved in pro-survival cellular pathways are commonly associated with pathologies, as the alteration of these routes compromises cellular homeostasis. This is the case of autophagy, an evolutionarily conserved pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 349 publications
(234 reference statements)
0
12
0
Order By: Relevance
“…Moreover, autophagy plays an indispensable role in cervical cancer as well ( 19 ). The effect of specific genes which take part in autophagy has become the focus of much research ( 20 ). Recently, the application of next-generation sequencing to an increasing number of cancer transcriptomes does indeed reveal that various cancer types are bound up with the unusual expression of thousands of lncRNAs ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, autophagy plays an indispensable role in cervical cancer as well ( 19 ). The effect of specific genes which take part in autophagy has become the focus of much research ( 20 ). Recently, the application of next-generation sequencing to an increasing number of cancer transcriptomes does indeed reveal that various cancer types are bound up with the unusual expression of thousands of lncRNAs ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified multiple pathogenic variants in autophagy-related genes that are involved in determining the risk of developing autoimmune diseases [ 219 , 220 , 221 , 222 ], cardiovascular diseases [ 223 , 224 ], neurodegenerative disorders [ 225 , 226 , 227 ], and different types of cancer (reviewed in [ 30 ] and later updated in [ 228 , 229 , 230 ]). However, despite the above evidence suggesting a key role of autophagy in the etiopathogenesis of hematological malignancies, the existence of a genetic component controlling this catalytic process in hemopathies has been poorly studied and is restricted to specific diseases [ 231 , 232 , 233 ].…”
Section: Germline Variation In Autophagy-related Genesmentioning
confidence: 99%
“…Autophagy proceeds through a series of sequential steps, including autophagosomal initiation and nucleation (phagophore formation), the elongation of the phagophore, the maturation of the double-membrane autophagosome with charge assimilation, and, finally the fusion of the autophagosome to the lysosome (autolysosome formation), culminating in the degradation of the components within the autolysosomes and their release into the cytosol [58]. Each of these steps is regulated by a variety of molecular components, such as the following: the Unc-51-like autophagy-activating protein kinase complex (ULK1/2); the class III phosphatidylinositol 3-kinase (PI3KC3) protein complexes; phosphatidylinositol 3-phosphate (PI(3)P)-binding proteins and ATG9-containing membranes; the ATG12 and ATG8 ubiquitin-like conjugation systems (UBL), essential for the formation of autophagosomes; selective autophagy receptors and factors involved in autophagosome-lysosome fusion, such as SNARE proteins, small GTPases, anchoring factors, and others [59].…”
Section: Autophagymentioning
confidence: 99%